Working with Academic Partners Effectively in the Context of Open Innovation: The Practice of Huawei - Adrian Furner; Yan Xu (International Telecommunications Society (ITS), 2018)
Huawei's Huawei Innovation Research Program (HIRP) has contributed to the development of Huawei from a Chinese start-up to a global ICT leader by lavaraging its cross-border and cross-cultural network connecting world-class scholars. With the help of HIRP, Huawei has acheived a large number of breakthroughs in both fundamental research and technology applications. The HIRP has acted as a systematic and transferable model to address the challenges of Academic-Industry partnership, with three consistent and consecutive approaches, namely shared objectives; relationship multiplier and portfolio-level connections. Our focus on the relationship as a key value differentiator has reduced the mismatch between Huawei and academia.This enhanced access to high quality academic partners enables the innovation of many game-changing technologies and leads to a Better Connected World.
Keywords: 330